Dot distribution maps to identify part-time distance learning programs (iCEPS) campuses in Universiti Teknologi MARA / Norasiah Mohammad and Ima Shafarhana Ibrahim - Mohammad, Norasiah; Ibrahim, Ima Shafarhana (Universiti Teknologi MARA, Perak, 2023)
The existing iCEPS webpage continues to display program information in a list format, requiring users to manually scroll through the list to access all the available UiTM programs. This presentation of data in a list format is inefficient for analysis as it necessitates users to imagine and visualize the geographical location of the campuses themselves. This study aims to investigate the feasibility of utilizing a dot distribution map to assist users (candidates) in their search and selection of campuses for pursuing part-time distance learning at the diploma or degree level, as offered by the Institute of Continuing Education and Professional Studies (iCEPS) at Universiti Teknologi MARA (UiTM). In this study, a methodology to enhance the user experience in selecting campuses for part-time distance learning programs at the diploma or degree level was implemented. This includes initializing a map using the Google Maps JavaScript API, generating markers on the map to represent campus locations, and implementing tooltips to provide essential information when users interact with the markers. The webpages with the dot distribution maps are presented as the findings of study. It is effectively visualizing the locations of iCEPS campuses across various branches in Peninsular Malaysia, Sabah and Sarawak. These dot distribution maps offer an interactive and user-friendly platform that allows users to access detailed information about the courses offered at each campus. The implications of this study point to a significant reduction in the time, costs, and health-related concerns associated with users' travelling. By providing an efficient means of campus selection through dot distribution maps, prospective learners can minimize the time spent commuting, reduce expenses on accommodation, food, and travelling thus promoting convenience, financial savings, and well-being.